A New Technique for Monitoring Bacteriological Quality of Water in Relation to Water-Borne Diseases - Gopal, Ram; Tak, T C; Bhutra, M (Annals of Arid Zone, 2016)
A rapid method for examination of faecal coliforms in water using a new chemically well-defined culture medium stable under extreme climatic conditions of desert is described. The presumptive test requiring 3 to 10 hr incubation at 40Â°C for faecal contamination is qualitative, quicker and simpler than existing standard methods. The confirmative test for Eschereclzia coli on agar plate requires incubation for another 8 to 10 hr at 40Â°C. The technique could be a good supplement to the existing methods in health centres towards control of water-borne diseases like typhoid, cholera and dysentery.